2016
DOI: 10.1007/s00134-016-4355-y
|View full text |Cite
|
Sign up to set email alerts
|

Nurses versus physician-led interhospital critical care transport: a randomized non-inferiority trial

Abstract: Purpose Regionalization and concentration of critical care increases the need for interhospital transport. However, optimal staffing of ground critical care transport has not been evaluated.MethodsIn this prospective, randomized, open-label, blinded-endpoint non-inferiority trial, critically ill patients on mechanical ventilation transported by interhospital ground critical care transport were randomized between transport staffed by a dedicated team comprising a critical care nurse and paramedic (nurses group)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
31
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 35 publications
0
31
0
2
Order By: Relevance
“…This means that in theory about half of the interhospital transports could be performed in the absence of a critical care physician. However, in the study of van Lieshout et al adverse events occurred in 15-16 % of transports in both groups [1]. In another study we found that the percentage of adverse events during transports performed with a dedicated MICU team was 12.5 % [2], and in a successive study most adverse events appeared to be caused by failure of technical equipment [3].…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…This means that in theory about half of the interhospital transports could be performed in the absence of a critical care physician. However, in the study of van Lieshout et al adverse events occurred in 15-16 % of transports in both groups [1]. In another study we found that the percentage of adverse events during transports performed with a dedicated MICU team was 12.5 % [2], and in a successive study most adverse events appeared to be caused by failure of technical equipment [3].…”
mentioning
confidence: 75%
“…Dear Editor, We compliment Van Lieshout et al on their study comparing the quality of interhospital critical care transports with a mobile intensive care unit (MICU) performed by a team comprising a critical care nurse and a paramedic or by team comprising a critical care nurse and a critical care physician [1]. The frequency of critical events did not differ between the groups.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…
Dear Editor, We thank Dr. Ligtenberg and colleges for their interest in our paper [1] and their subsequent correspondence [2], in which they comment on whether results of our study indicate that transports of critically ill patients in stable hemodynamic and respiratory condition with a mobile intensive care unit (MICU) can be safely performed by a team with a critical care nurse and a paramedic.We agree that a MICU represents a setting with limited personnel resources in the case the occurence of a critical event. Thereby, the authors' concern on the safety issue is well taken and indeed reflects the rationale of this trial.

We would like to stress that the objective of our study was not to detect a difference between the outcomes of two transport options using a classical superiority trial design, but to establish whether the omission of a critical care physician during MICU transports does not worsen the current transport protocol, which includes a physician.

…”
mentioning
confidence: 99%
“…Dear Editor, We thank Dr. Ligtenberg and colleges for their interest in our paper [1] and their subsequent correspondence [2], in which they comment on whether results of our study indicate that transports of critically ill patients in stable hemodynamic and respiratory condition with a mobile intensive care unit (MICU) can be safely performed by a team with a critical care nurse and a paramedic.…”
mentioning
confidence: 99%